Producing Detroit: Narratives of Space and Place in the 1932 Ford Hunger March and Funeral Protest. Issue 2 (4th May 2021) - Keohane, Jennifer
ABSTRACT: This paper explores competing narratives of the Detroit community after a deadly labor protest against the Ford Motor Company in 1932. Both mainstream and radical newspapers negotiated the meaning of violence through rhetorics of place. Mainstream papers defined protestors as a mob unduly influenced by Communist outsiders, which set up redemption for the police as Detroit's protectors. Radical journalists re-mapped Detroit to emphasize genuine working-class radicalism and set Henry Ford at the center of a transnational conspiracy. Considering place in the newspaper coverage allows rhetoricians to explore intersections of identity and materiality in labor rhetoric and understand the clashing rhetorical forces of worker solidarity and anti-communism.